Going Global: International WIL building future health work force capacity - Tomlinson, Kristy; Tan, Boon-Kiang; Flavell, Helen (Australian Collaborative Education Network, 2014)
In recognition of escalating globalisation and a growing diversity in local populations, there is demand for healthcare professionals with cultural competence. Universities have therefore begun incorporating international work-integrated learning (WIL) experiences into their curricula to produce ‘employable’ graduates for the global environment. While anecdotal evidence suggests students develop practical skills and capabilities as a result of international WIL, there is little empirical research investigating the degree to which this occurs, the specific learning benefits, and the components of international WIL that contribute to this learning. This study aimed to investigate how Health Science graduates and teaching staff perceived the value of an international WIL experience in building generic graduate attributes. Questionnaires using the Graduate Employability Indicators were completed by graduates and teaching staff to measure their perceptions of the extent to which international WIL contributes to the attainment of graduate attributes. Findings of this study indicate that graduates and teaching staff perceive that international WIL experiences enhance important graduate attributes including intercultural understanding, understanding different social contexts, contributing to the welfare of communities, teamwork, problem solving and thinking critically and analytically. This suggests that international WIL can facilitate the development of key graduate attributes that will serve to build the capacity of the future health workforce for a global environment.